2020
DOI: 10.1093/nop/npaa021
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of prognosis and goal of treatment in patients with malignant gliomas and their caregivers

Abstract: Background Patients with malignant gliomas have a poor prognosis. However, little is known about patients’ and caregivers’ understanding of the prognosis and the primary treatment goal. Methods We conducted a prospective study in patients with newly diagnosed malignant gliomas (N = 72) and their caregivers (N = 55). At 12 weeks after diagnosis, we administered the Prognosis and Treatment Perceptions Questionnaire to assess un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
2
18
1
Order By: Relevance
“…Other studies in caregivers of patients with hematologic malignancies have shown that caregivers' prognostic awareness is not associated with their distress. 33,34 Some oncologists may be concerned that having discussions focused on prognosis may take away hope or cause despair; however, our study findings do not support this notion. Importantly, most participants in this study wanted to know as many details as possible related to their diagnosis and treatment and valued knowing about their prognosis.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Other studies in caregivers of patients with hematologic malignancies have shown that caregivers' prognostic awareness is not associated with their distress. 33,34 Some oncologists may be concerned that having discussions focused on prognosis may take away hope or cause despair; however, our study findings do not support this notion. Importantly, most participants in this study wanted to know as many details as possible related to their diagnosis and treatment and valued knowing about their prognosis.…”
Section: Discussioncontrasting
confidence: 85%
“…Interestingly, when examining patient-caregiver dyads, caregivers reported a more accurate understanding of the patients' prognosis, similar to prior studies in patients with other incurable malignancies. 33,34 It is also possible that patients and caregivers may not interpret the terms "curable" and "terminal" similarly to clinicians, and that may reflect the limitation of our capacity to measure prognostic perceptions in this population. 35,36 The discrepancy between hearing the patients' cancer is incurable and reporting that the patient's disease is curable may also reflect cognitive dissonance and the internal conflict that caregivers experience as they process their loved ones' prognosis but still hope for a possibility of a cure.…”
Section: Discussionmentioning
confidence: 99%
“…To accommodate these different patient perspectives, an individual needs assessment is imperative when providing decision support such as SDM and the use of PtDAs [ 40 ]. Another issue to consider when involving family members is the potential discrepancy between the patient’s and the family’s perspectives on prognosis and treatment expectations related to the options [ 38 , 39 , 41 , 42 ]. Information preferences may differ between patients and their families [ 43 ], highlighting the importance of clinicians eliciting the two parties’ preferences for information and involvement (step 2 in the PtDA).…”
Section: Discussionmentioning
confidence: 99%
“…An emphasis on no treatment as a valid option in every treatment discussion is essential in PtDAs and SDM in general [ 45 , 46 ]. Previous research suggests that patients with HGG tend to overestimate the benefits of potential treatments while underestimating their disadvantages, which increases the risk of patients making decisions based on false perceptions [ 41 ]. Moreover, advanced cancer patients experience situations where the clinician does not explicitly present the pros and cons of ending active tumor treatment but merely informs these patients about the pros and cons of continuing treatment [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, this also relates to the autonomy and independence in the way physicians work. Nevertheless, thorough documentation is crucial and it is alarming when up to 80% of patients with advanced stage metastatic lung and GI cancers and malignant gliomas may not realize that their chemotherapy is probably not curative [ 12 , 52 ]. Studies also show that patients who have discussed the future with their doctor more recently or before the disease is too far advanced, have a more realistic understanding [ 53 ].…”
Section: Discussionmentioning
confidence: 99%